Financing Strategy for White Pomfretfish (Pampus Argenteus) Fishing Business at the Pasir Fish Landing Base Kebumen - Lukman Hakim, Ahmad Rendra; Nurani, Tri Wiji; Wisudo, Sugeng Hari; Darmawan, Darmawan (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2024)
Kebumen Waters is a coastal area in the southern part of Central Java, where white pomfret (Pampus argenteus) is the main commodity. However, its potential has not been fully optimized to support the fishermen's economy due to capital issues. This study employs interviews and field observations to collect data from relevant agencies, with respondents selected through the purposive sampling of 16 fishermen. The research findings indicate that the white pomfret fishery at PPI Pasir operates using 1 GT boat equipped with gill nets that have mesh sizes of 4.5–6.5 inches. The feasibility analysis reveals a profit of IDR 2,658,720.00 and an R/C of 1.03, confirming that the white pomfret fishery at PPI Pasir is viable for continuation. Three financing patterns for the fishermen's businesses at PPI Pasir have been identified, operational supplier financing, banking financing, and non-formal institutional financing, with non-formal institutions being the most advantageous source of funding. However, this type of non-formal financing has the drawback that fishermen do not receive their full income, making it necessary to synchronize all available funding sources at PPI Pasir.